Transcriptomic sequencing reveals that WNK2 promotes reactive oxygen species production in ovarian cancer cells - LI Fengjie; JIA Yongqin; WANG Yanzhou; DU Xiurong (陆军军医大学学报, 2023)
Objective To investigate the biological and metabolic roles of WNK2 in regulation of ovarian cancer based on transcriptome sequencing technology. Methods Ovarian cancer SKOV3 cells were divided into experimental group and control group, with 3 replicates in each group.The expression of WNK2 was knocked down with transfection of siRNA targeting WNK2 in SKOV3 cells.Then the total RNA was extracted and prepared for transcriptome sequencing and bioinformatics analysis after 48 h of transfection.The differential genes between siNC and siWNK2 were screened out in the range of padj < 0.01, fold change >1, and FPKM >500 to obtain the genes under the regulation of WNK2.DisGeNET and disease ontology (DO) enrichment analysis was used to analyze the relationship of the diseases and differentially expressed genes (DEGs).GO enrichment analysis was adopted to analyze the cellular functions and metabolic processes in which the DEGs were enriched.Finally, RT-qPCR was used to examine whether the 10 differential proteins in the reactive oxygen species (ROS) pathway were regulated by WNK2.The influence of WNK2 overexpression and knockdown on the ROS metabolic process of ovarian cancer cells was determined. Results The DisGeNET and DO enrichment analysis showed the obtained DEGs were closely related with malignant tumors (P < 0.05).GO functional enrichment analysis showed the obtained DEGs were enriched in biological processes such as ROS metabolism, apoptosis signaling pathway, formation of ubiquitin ligase complex and mitochondrial membrane protein complex, growth factor binding, and transcription activator activity and so on (P < 0.05).Among these enriched pathways, ROS related pathways were the most numerous and significant (P < 0.001).The results of RT-qPCR indicated that the changes in 9 DEGs were consistent with the sequencing results after WNK2 was knocked down, and one gene (PDGFB) was contrary to the sequencing results, and one gene had no significant change between the 2 groups.Knockdown of WNK2 in SKOV3 and CAOV3 cells resulted in decreased production of ROS, whereas overexpression of WNK2 increased the production. Conclusion WNK2 probably promotes ovarian cancer malignancy by inducing ROS metabolism.